2015
DOI: 10.1007/s11764-015-0432-4
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of cancer survivorship activities across national comprehensive cancer control programs

Abstract: Introduction Centers for Disease Control and Prevention’s (CDC) National Comprehensive Cancer Control Program (NCCCP) funds states, the District of Columbia, tribal organizations, territories, and jurisdictions across the USA develop and implement jurisdiction-specific comprehensive cancer control (CCC) plans. The objective of this study was to analyze NCCCP action plan data for incorporation and appropriateness of cancer survivorship-specific goals and objectives. Methods In August 2013, NCCCP action plans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…5 The authors noted that SCP use was negatively associated with freestanding cancer program type as compared with academic institutions. 6 Although the percentages of providers reporting the use of SCP should increase over time per IOM guidelines, the content and method of delivery of SCPs continue to evolve.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 The authors noted that SCP use was negatively associated with freestanding cancer program type as compared with academic institutions. 6 Although the percentages of providers reporting the use of SCP should increase over time per IOM guidelines, the content and method of delivery of SCPs continue to evolve.…”
mentioning
confidence: 99%
“…Approximately 64% of all plans included recommendations from four public health areas: surveillance and applied research; communication, education, and training; programs, policies and infrastructure; and access to high-quality care and services. 6 The CDC has prioritized projects that support receipt of appropriate care among survivors as well as meeting survivors’ psychosocial and supportive needs.…”
mentioning
confidence: 99%
“…The NAPCS recommends strategies focused on 4 core public health areas: 1) surveillance and applied research; 2) communication, education, and training; 3) programs, policies, and infrastructure; and 4) access to quality care and services. The majority (94%) of cancer coalitions supported by the NCCCP currently are working within their communities to pursue these public health strategies in support of cancer survivors . A recent assessment of the implementation of NAPCS revealed that 64% of NCCCP grantees include NAPCS strategies in their own program action plans .…”
Section: Cancer Control Programsmentioning
confidence: 99%
“…The majority (94%) of cancer coalitions supported by the NCCCP currently are working within their communities to pursue these public health strategies in support of cancer survivors . A recent assessment of the implementation of NAPCS revealed that 64% of NCCCP grantees include NAPCS strategies in their own program action plans . For example, grantees in New Mexico, South Carolina, Vermont, and Washington state and from the Fond Du Lac tribe have each implemented activities in all 4 of the NAPCS's strategy areas …”
Section: Cancer Control Programsmentioning
confidence: 99%
See 1 more Smart Citation